Subunit Interfaces Contribute Differently to Activation and Allosteric Modulation of Neuronal Nicotinic Acetylcholine Receptors - Short, Caitlin A. (Neuropharmacology, 2014)
Neuronal nicotinic acetylcholine receptors (nAChRs) are widely distributed in the nervous system and are implicated in many normal and pathological processes. The structural determinants of allostery in nAChRs are not well understood. One class of nAChR allosteric modulators, including the small molecule morantel (Mor), acts from a site that is structurally homologous to the canonical agonist site but exists in the β(+)/α(–) subunit interface. We hypothesized that all nAChR subunits move with respect to each other during channel activation and allosteric modulation. We therefore studied five pairs of residues predicted to span the interfaces of α3β2 receptors, one at the agonist interface and four at the modulator interface. Substituting cysteines in these positions, we used disulfide trapping to perturb receptor function. The pair α3Y168-β2D190, involving the C loop region of the β2 subunit, mediates modulation and agonist activation, because evoked currents were reduced up to 50% following oxidation (H(2)O(2)) treatment. The pair α3S125-β2Q39, below the canonical site, is also involved in channel activation, in accord with previous studies of the muscle-type receptor; however, the pair is differentially sensitive to ACh activation and Mor modulation (currents decreased 60% and 80%, respectively). The pairs α3Q37-β2A127 and α3E173-β2R46, both in the non-canonical interface, showed increased currents following oxidation, suggesting that subunit movements are not symmetrical. Together, our results from disulfide trapping and further mutation analysis indicate that subunit interface movement is important for allosteric modulation of nAChRs, but that the two types of interfaces contribute unequally to receptor activation.